EVALUASI KINERJA JALAN TAN MALAKA SIMPANG PARIK KOTA PAYAKUMBUH - Elvi Syamsuir; Sri Tria Siska (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Land Use Transportation is one of the important things in the development of land transportation, where land use can generate generation, especially in traffic. Movement occurs due to land use due to the presence of office, trade, tourism, industry and housing centers. One of the traffic activities whose land use area is busy being passed is the City of Payakumbuh. Payakumbuh city experienced very rapid development in the economic field. With the development, several roads in the city of Payakumbuh are busy with traffic volume and experience traffic jams. One of these roads is the Tan Malaka Simpang Paring Payakumbuh road, where this road can lead to several accesses including to the Riau province area. For this reason, a survey was carried out on the geometric conditions and traffic volume of the road to find out whether the performance of the road is in good condition or not and whether or not traffic management is needed. From observations and measurements, the width of Jalan Tan Malaka Simpang Parik is 7 meters with 2 lanes where each lane has the same width, namely 3.5 meters. The road has shoulders with the same width of 1.5 meters each. For the results of the traffic volume survey, data were obtained at 2582.6 pcu / hour. Meanwhile, from the analysis of road performance data, the degree of saturation is 1.041, meaning that the road is in a saturated condition.